2018
DOI: 10.1038/s41598-018-36117-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the Ranging behaviour and habitat use of the Ethiopian hedgehog (Paraechinus aethiopicus) in Qatar with hedgehog taxa from temperate environments

Abstract: We investigated seasonal changes in the ecology and behaviour of the Ethiopian hedgehog (Paraechinus aethiopicus) in Qatar, particularly in respect to differences in behaviour between hedgehogs living in arid environments and hedgehogs in temperate mesic environments. These comparisons will allow us to explore behavioural adaptations to different environments across hedgehog taxa. We radio-tracked 30 hedgehogs in Qatar over two years, and measured home range size, habitat preference, travel speed, activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 36 publications
(43 reference statements)
4
14
0
Order By: Relevance
“…Thus, P. aethiopicus is related to real desert environments. These remarks are in agreement with the observations of other authors who found the same preferences in this hedgehog in Qatar (Abu‐Baker, Reeve, Conkey, Macdonald, & Yamaguchi, ; Pettett, Al‐Hajri, Al‐Jabiry, Macdonald, & Yamaguchi, ). The Saharo‐Arabian origin of this species can explain its preferences and its local distribution.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, P. aethiopicus is related to real desert environments. These remarks are in agreement with the observations of other authors who found the same preferences in this hedgehog in Qatar (Abu‐Baker, Reeve, Conkey, Macdonald, & Yamaguchi, ; Pettett, Al‐Hajri, Al‐Jabiry, Macdonald, & Yamaguchi, ). The Saharo‐Arabian origin of this species can explain its preferences and its local distribution.…”
Section: Discussionsupporting
confidence: 93%
“…The Saharo‐Arabian origin of this species can explain its preferences and its local distribution. Ethiopian hedgehog can exploit a large home range than other Erinaceidae in case of lack in resource availability (Pettett et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Process of the search and selection of documents, n = 7[63][64][65][66][67][68][69], n = 18[70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87], n = 10[45,46,61,62,[88][89][90][91][92][93].…”
mentioning
confidence: 99%
“…Extensive research on the European hedgehog (Erinaceus europaeus) has led to the common notion that hedgehogs are characteristic of the moist temperate environments of the world. However, many hedgehog species occur in arid and semi-arid environments, such as the "desert hedgehogs" of the genus Paraechinus, and yet, little is known about their ecology and behavior in these arid environments [1][2][3][4][5][6][7][8][9][10]. More than 25 years ago, in his monograph of hedgehogs, Reeve (1994) [1] expressed his frustration by stating "There is a frustrating lack of further studies .…”
Section: Introductionmentioning
confidence: 99%
“…There is a clear need for much more fundamental work on all these and other, as yet unstudied, hedgehog species". Sadly, although there has been some work on ecology, behavior, and physiology of non-European hedgehog species in the past 25 years [3][4][5][6][7][8][9][10][11][12][13], basic information about their population characteristics is still largely lacking.…”
Section: Introductionmentioning
confidence: 99%